Freeze-Thaw-Induced Physically Cross-linked Superabsorbent Polyvinyl Alcohol/Soy Protein Isolate Hydrogels for Skin Wound Dressing: In Vitro and in Vivo Characterization - Varshney N.; Sahi A.K.; Poddar S.; Vishwakarma N.K.; Kavimandan G.; Prakash A.; Mahto S.K. (My University, 2025)
In this work, polyvinyl alcohol (PVA)- and soy protein isolate (SPI)-based scaffolds were prepared by physical cross-linking using the freeze-thaw method. The PVA/SPI ratio was varied to examine the individual effects of the two constituents. The physicochemical properties of the fabricated scaffolds were analyzed through Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction, thermogravimetric analysis, and differential scanning calorimetry. The SPI concentration significantly affected the properties of scaffolds, such as the extent of gelation (%), pore size, porosity, degradation, swelling, and surface wettability. The in vitro degradation of fabricated hydrogels was evaluated in phosphate-buffered saline and lysozyme solution for a duration of 14 days. The in vitro compatibility of prepared hydrogels was evaluated by the MTT assay with NIH-3T3 cells (fibroblast). The water vapor transmission rate (WVTR) assays showed that all hydrogels possessed WVTR values in the range of 2000-2500 g m-2 day-1, which is generally recommended for ideal wound dressing. Overall, the obtained results reveal that the fabricated scaffolds have excellent biocompatibility, mechanical strength, porosity, stability, and degradation rate and thus carry enormous potential for tissue engineering applications. Furthermore, a full-thickness wound healing study performed in rats supported them as a promising wound dressing material. © 2022 American Chemical Society.